2016
DOI: 10.1101/057992
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Situ Replication Rates for Uncultivated Bacteria in Microbial Communities

Abstract: Abstract:Culture-independent microbiome studies have revolutionized our understanding of the complexity and metabolic potential of microbial communities, but information about in situ growth rates has been lacking. Here, we show that bacterial replication rates can be determined using genome-resolved metagenomics without requirement for complete genome sequences. In human infants, we detected elevated microbial replication rates following administration of antibiotics, and bacterial growth rate anomalies prior… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…For example, clade 1 is associated with six metagenomes of the upper troposphere and clade 2 is associated with three metagenomes of thiocyanate bioreactor communities (see Table S2 ). In the case of clade 2, we conclude that D. acidovorans was native to the sample because the population was growing rapidly, on the basis of differential coverage at the origin and terminus of replication (peak-to-trough ratios [PTRs]) (full range, 1.5 to 1.9) ( 27 , 28 ) (see Table S4 ). In contrast, bacteria of the contaminant clade (clade 5) had consistently low growth rates, based on PTRs between 1.4 and 1.1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, clade 1 is associated with six metagenomes of the upper troposphere and clade 2 is associated with three metagenomes of thiocyanate bioreactor communities (see Table S2 ). In the case of clade 2, we conclude that D. acidovorans was native to the sample because the population was growing rapidly, on the basis of differential coverage at the origin and terminus of replication (peak-to-trough ratios [PTRs]) (full range, 1.5 to 1.9) ( 27 , 28 ) (see Table S4 ). In contrast, bacteria of the contaminant clade (clade 5) had consistently low growth rates, based on PTRs between 1.4 and 1.1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous analysis revealed that antibiotic administration is associated with elevated replication rates of gut organisms, which was hypothesized to be due to high resource availability after elimination of antibiotic susceptible strains 36 . We show here that a sample's mean replication index in the days following antibiotic treatment is positively correlated with total resistance gene content (p < 0.05) (Fig 3A).…”
Section: Major Facilitator Superfamily Pumps Are Associated With Incrmentioning
confidence: 99%
“…We show here that a sample's mean replication index in the days following antibiotic treatment is positively correlated with total resistance gene content (p < 0.05) (Fig 3A). The replication index, or iRep value 36 , is influenced by the fraction of cells in the population that are replicating. Our results suggest that the elevated iRep values after antibiotic treatment are likely not solely explained by resource availability, but rather appear to be influenced by the organisms' resistance gene sets.…”
Section: Major Facilitator Superfamily Pumps Are Associated With Incrmentioning
confidence: 99%
See 2 more Smart Citations